SOLVENT GUIDED EXTRACTS OF TWO OCIMUM SPECIES REVEALED VARIATIONS IN ANTIOXIDANT AND ANTIMICROBIAL PROPERTIES - Sumitra Pandaa; Jyotirmayee Lenka
The present study investigates the comparative antioxidant and antimicrobial potential in different solvent extracts of Ocimum sanctum and Ocimum basilicum collected from southeastern ghats highland agroclimatic zone of Odisha state, India. Extracts were prepared using solvents of increasing polarity, such as n-hexane, chloroform, ethyl acetate, methanol and water. DPPH (2,2-diphenyl-1-picrylhydrazyl) assay showed high antioxidant activity in methanolic extract of O. sanctum (IC50: 3.64 (So(Bg mL-1) and highest potency in ethyl acetate extract (IC50: 3.98 (So(Bg mL-1) of O. basilicum. Methanolic extracts of both species showed highest antimicrobial activity against Staphylococcus aureus and Escherichia coli (MIC: 6.25 (So(Bg mL-1, MBC: 12.5 (So(Bg mL-1). Methanolic extracts have highest phenolic and flavonoid content in O. basilicum (135.57 mg GAE g-1, 89.44 mg QE g-1) and O. sanctum (130.9 mg GAE g-1, 82.9 mg QE g-1). Solvent-guided extraction revealed significant variation in bioactivities, which could be analyzed in depth towards future improvement in drug discovery and as sustainable bioactive agents for therapeutic and industrial applications.s